EFISIENSI DAN EFEKTIVITAS PERENCANAAN ANGGARAN PENDAPATAN BELANJA NEGARA DI ERA DIGITAL: STUDI TERHADAP TRANSFORMASI DIGITALISASI FISKAL DI INDONESIA - Muslimin, M Iksan; Pratama, Inka Nusamuda; Ardiani, Yeni; Rahmania, Siti; Anjani, Hayaullah; Imara, Inang Sri; Jeriyah, Ainul; M Samunawardin; Imran, Imran; Marzuki; Tiara; Isdin (Yayasan Nusantara Hasana Berdikari, 2025)
Current developments in technology and information bring rapid and dramatic changes from traditional analog to digital in the digital era. Digitalization of information is the process of changing various analog formats to digital so that it can be easily created, stored, managed and distributed to users for various purposes and as a basis for decision making. The methodology used in assessing the efficiency and effectiveness of APBN planning in the digital era is through a literature review approach collect, analyze and integrate various relevant literature sources, both from journals, articles, books and previous research reports. The real result of digitalization is the reduction in time needed to prepare and allocate the national budget. The electronic budget system introduced by the Indonesian Ministry of Finance allows faster and more transparent budget allocation, thereby reducing the need for time-consuming manual procedures. Developing human resources, strengthening research and innovation, and developing systems and technology are important foundations for implementing digital transformation. Successful digital transformation requires people who are willing to change and learn to use digital products. In this regard, the Indonesian government has implemented various steps to increase digital literacy both at the government level and digital training for small and medium enterprises (SMEs).